2007
DOI: 10.1189/jlb.0507276
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A inhibits apoptosis of human neutrophils via a P2X7-sensitive pathway independent of formyl peptide receptor-like 1

Abstract: Neutrophil apoptosis is important for the termination of inflammatory reactions, in that it ensures placid clearance of these potently cytotoxic cells. Various proinflammatory cytokines delay neutrophil apoptosis, which may result in accumulation of these cells, sometimes accompanied by tissue destruction, potentially leading to various inflammatory disease states. Rheumatoid arthritis (RA) is characterized frequently by elevated levels of the acute-phase reactant serum amyloid A (SAA) in circulation and in ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 57 publications
1
76
0
1
Order By: Relevance
“…8,41,42 In contrast to CRP, SAA is more often discussed as causal factor for cardiovascular disease. 15,16,43 Furthermore, SAA exhibits pro-inflammatory characteristics such as the attraction of phagocytes, the induction of proinflammatory cytokines and the delay of neutrophil apoptosis, 11,12 which may contribute to the pathogenesis of atherosclerosis. SAA has been reported to act pro-atherogenic also by driving an increase in vascular biglycan content, predisposing the vessel wall to increased retention of atherogenic lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,41,42 In contrast to CRP, SAA is more often discussed as causal factor for cardiovascular disease. 15,16,43 Furthermore, SAA exhibits pro-inflammatory characteristics such as the attraction of phagocytes, the induction of proinflammatory cytokines and the delay of neutrophil apoptosis, 11,12 which may contribute to the pathogenesis of atherosclerosis. SAA has been reported to act pro-atherogenic also by driving an increase in vascular biglycan content, predisposing the vessel wall to increased retention of atherogenic lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…10 Further suggested functions of SAA comprise chemotaxis for monocytes and neutrophils, the promotion of pro-inflammatory cytokine expression, and the prolongation of the lifespan of neutrophils through an antiapoptotic effect. 11,12 Elevated SAA levels are implicated in several chronic inflammatory diseases, such as amyloidosis, atherosclerosis, rheumatoid arthritis and chronic obstructive pulmonary disease (COPD), 12,13 suggesting that SAA may have an active role in these diseases. Similar to CRP, SAA is a biomarker for the prediction of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…SAA1 and pro-inflammatory chemokines IL8, CCL2, CXCL5, CXCL3, CXCL2 and CCL8 belong to the top-ten most up-regulated genes (see Table 3), SAA1 being the most up-regulated gene with a 27-fold change by comparison to mock-stimulated PBMCs. SAA1 encodes the major acute-phase protein Serum Amyloid A (SAA), the precise role of which is still unclear despite reports suggesting a key role in the establishment and maintenance of inflammation notably as an antiapoptotic agent for neutrophils [36] and as an opsonin that would facilitate phagocytosis of gram-negative bacteria [37]. SAA1 was also found as the most up-regulated gene in spleen seven days after infection by H. parasuis [9].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to FPR2, several other targets have been reported as specific receptors for SAA, including receptor for advanced glycation end products (Yan et al, 2000), the HDL receptor, scavenger receptor class B type I (Cai et al, 2005), CLA-1 (CD36 and LIMPII analogous-1), human orthologue of the Scavenger Receptor Class B Type I (Baranova et al, 2005), P2X7 (Christenson et al, 2008), TLR4 (Sandri et al, 2008), and TLR2 (He et al, 2009). Because we found that SAA stimulated CCL2 production via a PTX-insensitive pathway, we confirmed a role for FPR2 in SAA-induced cellular signaling in HUVECs.…”
Section: Discussionmentioning
confidence: 99%